All Days 2014
DOI: 10.2118/169694-ms
|View full text |Cite
|
Sign up to set email alerts
|

Recovery Factor Estimation in EOR Polymerflood Project: Field Case

Abstract: A chemical Enhanced Oil Recovery process by means of polymerflooding has been implemented successfully in a large sandstone field in the south of Oman since 2010. To date, very good response was observed from the polymer flood due to improved sweep efficiency. A common measure of success for such a chemical EOR process is the incremental oil Recovery Factor over the existing mature waterflood. One of the challenges in this EOR project is the estimation of the incremental oil reserves attributed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Despite the productivity losses documented in Bohai Bay, Marmul and SHRU polymer floods, these projects have been reported as technical and economic successes (Al-Saadi et al, 2014;Christopher et al, 1988;Xiaodong et al, 2011). Additionally, Choudhuri et al (2014) reported the optimization of the current phase (27 patterns) of the polymer flood based on streamline simulation.…”
Section: Summary Discussionmentioning
confidence: 99%
“…Despite the productivity losses documented in Bohai Bay, Marmul and SHRU polymer floods, these projects have been reported as technical and economic successes (Al-Saadi et al, 2014;Christopher et al, 1988;Xiaodong et al, 2011). Additionally, Choudhuri et al (2014) reported the optimization of the current phase (27 patterns) of the polymer flood based on streamline simulation.…”
Section: Summary Discussionmentioning
confidence: 99%